Neural congruency effects in the multi-source interference task vanish in healthy youth after controlling for conditional differences in mean RT. - Kamin Kim (PLoS ONE, 2013)
According to the conflict monitoring model of cognitive control, reaction time (RT) in distracter interference tasks (e.g., the Stroop task) is a more precise index of response conflict than stimulus congruency (incongruent vs. congruent). The model therefore predicts that RT should be a reliable predictor of activity in regions of the posterior medial frontal cortex (pMFC) that are posited to detect response conflict. In particular, pMFC activity should be (a) greater in slow-RT than in fast-RT trials within a given task condition (e.g., congruent) and (b) equivalent in RT-matched trials from different conditions (i.e., congruent and incongruent trials). Both of these effects have been observed in functional magnetic resonance imaging (MRI) studies of adults. However, neither effect was observed in a recent study of healthy youth, suggesting that (a) the model does not accurately describe the relationship between RT and pMFC activity in this population or (b) the recent study was characterized by high variability due to a relatively small sample size. To distinguish between these possibilities, we asked a relatively large group of healthy youth (n = 28) to perform a distracter interference task - the multi-source interference task (MSIT) - while we recorded their brain activity with functional MRI. In this relatively large sample, both of the model's predictions were confirmed. We conclude that the model accurately describes the relationship between pMFC activity and RT in healthy youth, but that additional research is needed to determine whether processes unrelated to response conflict contribute to this relationship.